Africa in Focus of International Broadcasting: Political and Media Dimensions of Neocolonialism - Tereshchuk, Vitalii (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The article examines the role and place of the African region as an object of international broadcasting. Various models of international broadcasting implementation in contemporary political conditions are shown on the example of countries — former metropolises of colonial empires that covered African territories. Among other things, the author shows that international broadcasting in Africa can be considered as an element of neo-colonialism.